Gestational diabetes with diabetes and prediabetes risks: A large observational study - Shen, Yun (Eur J Endocrinol, 2018)
AIMS: To compare risks of early postpartum diabetes and prediabetes in Chinese women with and without gestational diabetes mellitus (GDM) during pregnancy SUBJECTS AND METHODS: Tianjin GDM observational study included 1263 women with a history of GDM and 705 women without GDM who participated in the urban GDM universal screening survey by using World Health Organization’s criteria. Postpartum diabetes and prediabetes were identified after a standard oral glucose tolerance test. Cox proportional hazards regression was used to assess risks of postpartum diabetes and prediabetes between women with and without GDM. RESULTS: During a mean follow-up of 3.53 years postpartum, 90 incident cases of diabetes and 599 incident cases of prediabetes were identified. Multivariable-adjusted hazard ratios among women with prior GDM, compared with those without it, were 76.1 (95% CI 23.6-246) for diabetes, and 25.4 (95% CI 18.2-35.3) for prediabetes. When the mean follow-up extended to 4.40 years, 121 diabetes and 616 prediabetes were identified. Women with prior GDM had a 13.0-fold multivariable-adjusted risk (95% CI 5.54-30.6) for diabetes and 2.15-fold risk (95% CI 1.76-2.62) for prediabetes compared with women without GDM. The positive associations between GDM and the risks of postpartum diabetes and pre-diabetes were significant and persistent when stratified by younger and older than 30 years at delivery, and normal weight and overweight participants. CONCLUSIONS: The present study indicated that women with prior GDM had significantly increased risks for postpartum diabetes and prediabetes, with the highest risk at the first 3-4 years after delivery, compared with those without GDM.